Curriculum Characteristics of Rural School Districts in Thirteen Selected States - Bruce Barker; Ivan Muse; Ralph Smith (Journal of Research in Rural Education, 1983)
This study gathered descriptive data from a random sample of K-12 public school districts of 900 students or fewer in the United States and compared these findings with data collected from similar sized districts in Arkansas, Colorado, Illinois, Iowa, Kansas, Missouri, Nebraska, New York, North Dakota, Oklahoma, Texas, Washington, and Wisconsin. The study focused on information about the rural district, the school superintendent, the teachers, student performance, and school programs. Data were collected during the 1982-83 school year.